Trends in the Association between Pyoderma Gangrenosum and Autoimmune Hepatitis: Case Report and Review of the Literature. Issue 5 (September 2014) - Wat, Heidi; Haber, Richard M.
Background: Pyoderma gangrenosum (PG) is a neutrophilic dermatosis commonly associated with underlying systemic illness, typically of autoimmune origin. The association of PG with autoimmune hepatitis (AIH) has been reported but remains poorly recognized. Observations: We describe a case of PG manifesting 5 years following the diagnosis of AIH and conduct a literature review to determine the significance of this association. We identified a predisposition for young females and a tendency for PG to arise 4 to 12 years after the diagnosis of AIH during a period of disease quiescence. Additionally, fulminant hepatitis as the initial presentation of AIH appears to be a risk factor in the subsequent development of PG. Conclusions: These observations may provide important clues for the pathogenesis of PG in the context of AIH. Recognition of this association has important implications for dermatologists in the evaluation, workup, and management of patients with a history of AIH and suspected PG.